Plasma metabolomics analyses highlight the multifaceted effects of noise exposure and the diagnostic power of dysregulated metabolites for noise-induced hearing loss in steel workers - Zhang, Xiuzhi; Li, Ningning; Cui, Yanan; Wu, Hui; Jiao, Jie; Yu, Yue; Gu, Guizhen; Chen, Guoshun; Zhang, Huanling; Yu, Shanfa (Frontiers in Molecular Biosciences, 2022)
Noise exposure can lead to various kinds of disorders. Noise-induced hearing loss (NIHL) is one of the leading disorders confusing the noise exposed workers. It is essential to identify NIHL markers for its early diagnosis and new therapeutic targets for its treatment. In this study, a total of 90 plasma samples from 60 noise-exposed steel factory male workers (noise group) with (NIHL group, n=30) and without NIHL (non-NIHL group, n=30) and 30 male controls without noise exposure (control group) were collected. Untargeted human plasma metabolomic profiles were determined with HPLC-MS/MS. The levels of the metabolites in the samples were normalized to total peak intensity and the processed data was subjected to multivariate data analysis. Wilcoxon test and orthogonal partial least square-discriminant analysis (OPLS-DA) were performed. With the threshold of p < 0.05 and variable importance of projection (VIP) value > 1, 469 differential plasma metabolites associated with noise exposure (DMs-NE) were identified and their associated 58 KEGG pathways were indicated. 33 differential metabolites associated with NIHL (DMs-NIHL) and their associated 12 KEGG pathways were identified. There were six common pathways associated with both noise exposure and NIHL. Through multiple comparisons, seven metabolites were shown to be dysregulated in NIHL group comparing with the other two groups. Through LASSO regression analysis, two risk models were constructed for NIHL status predication which could discriminate NIHL from non-NIHL workers with area under the curve (AUC) of 0.840 and 0.872, respectively, indicating their efficiency in NIHL diagnosis. To validate the results of the metabolomics, cochleae gene expression comparisons between susceptible and resistant mice in GSE8342 dataset from gene expression omnibus (GEO) were performed. The immune response and cell death related processes were highlighted for their close relations with noise exposure, indicating their critical roles in noise-induced disorders. We concluded that there was significant difference between the metabolite’s profiles between NIHL cases and non-NIHL individuals. Nosie exposure could lead to dysregulations of a variety of biological pathways, especially immune response and cell death related processes. Our results might provide new clues for noise exposure study and NIHL diagnosis.